Malinalli - Chapa, Veronica (Primero Sueño Press, Atria, 2025)
"A real-life historical figure, the woman known as Malinalli, Malintzin, La Malinche, Doña Marina, and Malinalxochitl was the Nahua interpreter who helped Spanish conquistador Hernán Cortés communicate with the native people of Mexico. When indigenous leaders observed her marching into their cities, they believed she was a goddess--blessed with the divine power to interpret the Spaniards' intentions for their land. Later, historians and pop culture would deem her a traitor--the "Indian" girl who helped sell Mexico's future to an invader. In this riveting, fantastical retelling, Malinalli is all of those things and more, but at heart, she's a young girl, kidnapped into slavery by age twelve, and fighting to survive the devastation wrought by both the Spanish and Moctezuma's greed and cruelty. Blessed with magical powers, and supported by a close-knit circle of priestesses, Mali vows to help defend her people's legacy. In vivid, compelling prose, debut author Veronica Chapa spins an epic tale of magic, sisterhood, survival, and Mexican resilience. This is the first novel to reimagine and reinterpret Malinalli's story with the empathy, humanity, and awe she's always deserved." --